Adoption of Supplementary Feeding in Smallholder Dairy Cattle Production in Mbarara District - Twesigye, Gilbert; Ssemakula, Edward; David, Bahame B. (American Journal of Agriculture, 2022)
This study sought to assess the level of adoption of supplementary feeding, associated socioeconomic factors and the relationship between supplementary feeding and dairy cattle production among smallholder dairy farmers in Mbarara District. Methodology: The study adopted a mixed approach to collect both quantitative and qualitative data from 198 smallholder farmers and 12 key informants using a semi-structured interview guide and key informant interview guide respectively. Cluster sampling was used to divide the target population into clusters and then selected elements from each cluster using Simple Random Sampling technique. Collected data was compiled, sorted, and entered into Statistical Package for Social Scientists (SPSSv26.0) for analysis. Findings: The study revealed that 81.3% of smallholder farmers adopted supplementary feeding. However, the level of supplementary feeding varied among smallholder farmers of different socioeconomic characteristics. Basically, there was low level of adoption of supplementary feeding among farmers with few household members, having little knowledge about supplementary feeding and little funds to finance the costs involved in application of supplementary feeds. In relation to dairy cattle production, there was a positive significant relationship between the level of adoption of supplementary feeding and milk yield. Unique contribution to practice and policy: This study suggests to policy makers and other relevant authorities to formulate polices that emphasize adoption of supplementary feeding among dairy farmers in order to increase milk production in cattle.
Keywords: Supplementary; Feeding; Smallholder; Adoption; Production